Ethnochemistry: Exploring the Potential of Sasak and Javanese Local Wisdom as a Source of Chemistry Learning to Improve the Learning Outcomes of Pre-Service Teachers - Dwi Wahyudiati*; Devi Qurniati (Jurnal Pendidikan Sains Indonesia, 2023)
Learning resource availability was still focused on abstract concepts without integrating them with students' daily experiences. This appears since the ethnochemistry approach implementation in universities is still rarely conducted.  The purpose of this study is to analyze the relevance of Sasak and Java local wisdom with chemistry and explore the potential of Sasak and Java local wisdom as a learning resource in basic chemistry courses. The data collection instruments were observation, interviews, and documentation. In analyzing the data, the researcher used the Spradley data analysis technique. The instruments were chosen based on their suitability with the type of data to be analyzed. Furthermore, the data analysis techniques consist of four stages, namely;(1) domain analysis; (2) taxonomic analysis; (3) componential analysis; and (4) cultural themes analysis. Based on the research findings, it proved that the local wisdom of Sasak and Java, which consists of cultural products and local wisdom values in Sasak and Java culture, has relevance to chemistry material that can be used as a learning resource. Research conclusions include: (1) The relevance of Sasak and Java local wisdom with basic chemistry material can be reviewed based on the perspective or analogy approach, representation, and visualization; and (2) the potential of Sasak and Java local wisdom as learning resources in basic chemistry courses includes three subjects, namely: material and its changes, the periodic system of elements, and chemical bonds integrated with Sasak and Java local wisdom